Computational and experimental approach for investigation of electronic and optical response of MgxCu2-xO. (1st February 2022) - Ramay, Shahid M.; Ali, Syed Mansoor; Sadjih, Ahmad M.; Kasim, Hamoud; Amer, Mabrook S.; Alam, Manawwer
Abstract: The electronic and optical characteristics of Cu2 O based semiconductor materials are recently focused on due to having applications in modern electronic devices and solar cells. In this study, Mg incorporated Cu2 O structures were simulated using density functional theory calculations for the prediction of electronic and optical response. The simulations were carried out using the generalized gradient approximation approach by considering the full-potential linearized augmented plane wave method. Pure and Mg incorporated Cu2 O thin films with 3.7, 5.5, and 12.5% Mg contents were deposited in uniform morphology using spin coating technique. Ab-initio and experimental investigations present a strong correlation of electronic and optical properties. The bandgap was observed to decrease with the incorporation of Mg in the Cu2 O structure. The absorption coefficient and real epsilon depict a sharp increment with Mg doping in the visible regime. The specific outcomes make these materials excellent candidates for dielectric and optoelectronic applications. Highlights: Ab-initio calculations of pure and Mg doped Cu2 O using Wien2k code. DOS spectra reveals the p-d hybridization between Cu and O atoms. Surface morphology reveals the uniform growth of thin films. Mg–Cu2 O thin films depict the reduced values of bandgap. The absorption coefficient and real epsilon were found to increase with Mg content.